2015
DOI: 10.1038/mt.2014.155
|View full text |Cite
|
Sign up to set email alerts
|

Interventional Magnetic Resonance Imaging-guided Cell Transplantation Into the Brain With Radially Branched Deployment

Abstract: Intracerebral cell transplantation is being pursued as a treatment for many neurological diseases, and effective cell delivery is critical for clinical success. To facilitate intracerebral cell transplantation at the scale and complexity of the human brain, we developed a platform technology that enables radially branched deployment (RBD) of cells to multiple target locations at variable radial distances and depths along the initial brain penetration tract with real-time interventional magnetic resonance image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…Beyond assessing the viability of the cells after passing through the system 20 , we were concerned as to whether the cells were affected by the time elapsed after their upload, as the best-planned surgery can run into delays. Our experiment demonstrated that cell viability is acceptable up to 2 h after being in the system, although some adhesion of neurospheres was observed.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond assessing the viability of the cells after passing through the system 20 , we were concerned as to whether the cells were affected by the time elapsed after their upload, as the best-planned surgery can run into delays. Our experiment demonstrated that cell viability is acceptable up to 2 h after being in the system, although some adhesion of neurospheres was observed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, great strides have been made towards the development and improvement of intraoperative MRI (iMRI) methods (Mislow et al 2009 ). Silvestrini et al (Silvestrini et al 2015 ) used real-time iMRI (RT-iMRI) for cell transplantation into a swine and cadaveric human head as a concept for application in the human brain. The platform technology utilizes a radially branched deployment strategy to access multi-directional deposit sites along a single cannula insertion tract.…”
Section: The Future Of Cbts and Nhp Studiesmentioning
confidence: 99%
“…Interventional MRI (iMRI) is a stereotactic neurosurgical technique that can be used to accurately implant DBS leads and deliver biologics with “real‐time” MR guidance and monitoring . For instance, with iMRI, the same skull‐mounted aiming device can be used for gene therapy infusion or cell delivery before DBS lead implantation . Given that the typical trajectories used for DBS lead implantation and biologic delivery to relevant PD brain targets are similar (Fig.…”
Section: Dbs Lead Implantation As a Surgical Control Group: Eliminatimentioning
confidence: 99%
“…13,32 For instance, with iMRI, the same skull-mounted aiming device can be used for gene therapy infusion or cell delivery before DBS lead implantation. 33 Given that the typical trajectories used for DBS lead implantation and biologic delivery to relevant PD brain targets are similar (Fig. 1B), one burr hole per hemisphere is likely to suffice.…”
Section: Dbs Lead Implantation As a Surgical Control Group: Eliminatimentioning
confidence: 99%